Pola Hubungan Antara Petani Karet Dengan Toke (Patron-Client) Di Desa Sawah Kecamatan Kampar Utara Kabupaten Kampar - Syafriyatin '; Yusmini '; Shorea Khaswari (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The purpose of this research is to know the factors of extracting and relationship between rubber farmers in the marketing of rubber traders (toke), for to know the mechanism of toke entry of the village as well as the problems faced by rubber farmers by using survey methods and questionnaires as a tool to answer purpose. The research was conducted at the Sawah Village Kampar Utara District of Kampar Region. In this study, the sampel was 3 people of toke in the village, 2 peoples of  toke out of village, and 15 peoples of rubber farmers. Data obtained from this study is primary data that interviews of sampels as well as secondary data from relevant agencies. Pull factors of the relationship between rubber farmers with Toke In the first factor is the provision of 100% holiday allowance, provision of debt factor 44.44%, factor family 22.22% and 11.11% factor of capital ownership which led to the patron-client relationship. The pull factor to the relationship between rubber farmers Toke Affairs is a higher price factor 100%. Factor driving the relationship between rubber farmers to toke in is because of low prices. factor driving the relationship between rubber farmers with the outside is because the good toke inside. The problems that occur in the rubber farmers sell to rubber because of debts of seller, short of capital, production facilities are not available and the price is determined unilaterally by toke. Keywords: marketing, patron-client, farmers, Toke